Relationships among thriving at work, organisational commitment and job satisfaction among Chinese front-line primary public health workers during COVID-19 pandemic: a structural equation model analysis - Di Jiang; Jingjing Wang; Lei Guo; Yuanmin Jia; Mo Yi; Zeyi Zhang; Ou Chen; Baosheng Zhao (BMJ Open)
Objectives This study aims to explore the mediating effect and influence mechanism of organisational commitment on the association among thriving at work and job satisfaction among frontline primary public health workers (PHWs) in China during the COVID-19 pandemic.Design This study is a cross-sectional written survey.Setting We included 20 primary care units in northern provinces of China.Participants A total of 601 PHWs who worked in primary organisations and against COVID-19 on the front line were included.Methods We collected the data from the participants’ written questionnaire (Minnesota Satisfaction Questionnaire, thriving at work scale and organisational commitment scale), and programmed AMOS V.26.0 to develop a structural equation model (SEM) based on the relationships among the three variables.Results The thriving at work scores of the primary PHWs were (M=3.17, SD=0.65), and job satisfaction was (M=3.05, SD=0.69); the scores of their thriving at work, organisational commitment and job satisfaction were all significantly correlated (p<0.01); and the SEM indicated that organisational commitment had a significant partial mediating effect between thriving at work and job satisfaction. The overall effect value was 0.867, and the mediated effect value was 0.422, accounting for 48.7% of the total effect size.Conclusion The thriving at work and job satisfaction scores of primary PHWs in China are moderate, and thriving at work not only affects job satisfaction directly, but also indirectly through organisational commitment. This study suggests that health policy-makers should promote job satisfaction among PHWs through relative inventions aiming to improve their thriving at work and organisational commitment.